Scholarly Responses To Allegations Against Imam Abū Ḥanīfa - Shibili MK (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2026)
Imam Abū Ḥanīfa was well profound scholar who was recognized as a founder of a flexible school of thought. It was prevailed so as to cover a wider area of Islamic civilization overtaking all other school of thought. His legal rulings always remained within the boundaries set by the Qur’an and the sunnah from. Unfortunately, his legacy was not free from criticism. he confronted some accusations even from great Islamic scholars. Throughout history, criticism against him erupted of two major factors: first, possessing insufficient knowledge of ḥadīth, and second, giving preference to qiyās (analogical reasoning) over prophetic traditions. This article aims to uncover causes of these accusations against him, evaluate historical contexts and authenticity of such statements attributed to prominent Islamic scholars and their late absolute acknowledgement, and to analyze the responses provided by classical and modern scholars in defense of Imam.